The prevalence of internet addiction and associated factors among undergraduate medical students in government medical college, Almora - Preeti; Masroof Hasan Khan; Mittal, Sneha; Vikram Singh Dhapola (Asian Journal of Medical Sciences, 2024)
Background: The internet, computers, smartphones, and other electronic device’s use has increased suddenly over recent decades. Although this increase has benefits to the users, but also excessive use often leads negative health consequences. Aims and Objectives: The objective of this study was to measure the prevalence of internet addiction (IA) and stress among undergraduate medical students. Materials and Methods: A descriptive cross-sectional study was conducted among 299 undergraduate medical students enrolled in the government medical college, Almora. A 20-item Young’s IA test which is a Likert scale-based interview schedule was used to measure the prevalence of IA and the perceived stress scale 14 scale is used to assess stress among them. Results: Among the 299 study subjects, 49.5% were males and 50.5% were females. Males were more addicted to the internet than females. The prevalence of IA among the study subjects in the present study was 45.4% mild, 13.8% moderate, while 40.8% of students reported normal internet usage. Conclusion: IA is a growing health problem among medical students these days, thus necessary preventive and therapeutic interventions are very important to promote healthy and safe usage of the internet.